DEPOSITO SEBAGAI JAMINAN KREDIT BERDASARKAN UNDANG-UNDANG PERBANKAN - Asuan, Asuan (Solusi, 2020)
Time deposit is a banking product, namely customers who deposit their money within a certain period of time in a bank (according to the agreement between the customer and the bank), which earns deposit interest. Deposits as collateral in the credit agreement between the debtor / customer and creditor / bank. in the provision of credit which may not exceed 95% of the value of deposits with a credit period of 60 months at the longest, based on Article 1 point 7 of Law Number 10 of 1998 concerning Banking. If there is a default based on article 1238 of the Civil Code, then the creditor as the credit provider commits legal actions, namely warning letters, summons and execution and settlement through a lawsuit to the Court, then through the State Receivables Affairs Committee and the State Receivables Affairs Committee based on Law Number 49 of the Year 1960 Concerning the Committee for State Receivables Affairs.